Studi Literature: Status Gizi pada Balita - Nanda Auliya Rosidin; Isroatul Koriah; Destia Milda Anggaraini Putri; Erma Putri Lestari; Nadia Intan Permata; Ida Sofiyanti (Universitas Ngudi Waluyo, 2024)
Nutritional status is a condition of the body caused by the balance between nutrient intake and needs. This balance can be seen from the growth variables, namely body weight, height/body length, head circumference, arm circumference, and leg length. This study shows that there is a relationship between knowledge and nutritional status of toddlers, there is a relationship between the role of cadres and nutritional status and there is a relationship between economic status and nutritional status of toddlers. It is very important to formulate appropriate policies and interventions. Effective interventions can help improve the quality of life and health of children in this area, as well as prevent long-term impacts caused by nutritional problems. Objective to find out what factors influence the nutritional status of toddlers in Indonesia, including environmental factors (region type), social and economic factors (maternal education level). Method; This research is a literature study through electronic media, Garuda and Google Scholar which were published between 2020 and 2024.Results; from 5 articles related to nutritional status in toddlers. Each article is related because it can examine the factors that cause nutritional deficiencies in toddlers which then function to reduce the occurrence of stunting in toddlers. Conclusion; From the overall review of the article, it shows that there are several factors related to nutritional status in toddlers. Abstrak Status gizi adalah suatu keadaan tubuh yang diakibatkan oleh keseimbangan antara asupan zat gizi dengan kebutuhan. Keseimbangan tersebut dapat dilihat dari variabel pertumbuhan, yaitu berat badan, tinggi badan/panjang badan, lingkar kepala, lingkar lengan, dan panjang tungkai.penelitian ini menunjukkan bahwa ada hubungan pengetahuan dengan status gizi balita, ada hubungan peran kader dengan status gizi dan ada hubungan status ekonomi dengan status gizi balita sangat penting untuk merumuskan kebijakan dan intervensi yang tepat. Intervensi yang efektif dapat membantu meningkatkan kualitas hidup dan kesehatan anakanak di daerah ini, serta mencegah dampak jangka panjang yang disebabkan oleh masalah gizi. Tujuannya untuk mengetahui faktor apa saja yang mempengaruhi status gizi pada balita di Indonesia antara lain, faktor lingkungan (tipe wilayah), faktor social dan ekonomi (Tingkat Pendidikan ibu ). Metode penelitian ini adalah penelitian studi literatur melalui media elektronik, , Garuda dan google scholar yang di publikasikan antara tahun 2020 hingga 2024. Hasil; dari 5 artikel yang berhubungan dengan status gizi pada balita .Setiap art ikel tersebut berhubungan karna dapat meneliti mengenai faktor terjadinya kekurangan zat gizi pada balita yang kemudian berfungsi untuk mengurangi terjadinya stanting pada balita. Kesimpulan dari tinjauan keseluruhan artikel, menunjukkan bahwa ada beberapa faktor yang berhubungan dengan status gizi pada balita.